2021
DOI: 10.3389/fonc.2021.742666
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemotherapy as a Trigger to Overcome Primary Resistance to Anti-PD-1 Treatment: A Case Report of Melanoma of the Scalp

Abstract: BackgroundImmunotherapy with immune checkpoint inhibitors is one of the main therapies for advanced melanoma. Nevertheless, albeit remarkable, immunotherapy results are still unsatisfactory as more than half of patients progress, and resistance to treatment still has a dramatic impact on clinical outcomes. Local treatments such as radiotherapy or electrochemotherapy (ECT), in addition to local control with palliative intent, have been shown to release tumoral neoantigens that can stimulate a robust systemic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Nearly complete response was eventually obtained after the treatment with ipilimumab and was present at 6-months followup (65). Two other case reports also demonstrated beneficial effects of combined treatment with electrochemotherapy and ICIs (66,67).…”
Section: Melanomamentioning
confidence: 85%
“…Nearly complete response was eventually obtained after the treatment with ipilimumab and was present at 6-months followup (65). Two other case reports also demonstrated beneficial effects of combined treatment with electrochemotherapy and ICIs (66,67).…”
Section: Melanomamentioning
confidence: 85%
“…A 39 year old patient with stage II metastatic melanoma was treated with PD-1 CPI and ECT as a 5th line treatment, and the patient does not show any sign of disease reoccurrence 4 years after the treatment [29]. A further case report indicated that repeat ECT treatments are still effective for local tumour burden reduction when being used before PD-1 CPI and also after PD-1 CPI [30]. Quaresmini et al concluded that their case report highlights the possibility of ECT to increase tumour immunogenicity, thus leading to an increase response to CPI.…”
Section: Developing Immune Co-treatments With Ect In Cancer Patientsmentioning
confidence: 99%
“…However no data from trials exist to evaluate the potential role of the combination or the correct sequence of these two therapeutic options-loco-regional and systemic treatment-but only anecdotic/retrospective cases in papers. Moreover, nowadays it is unknown the appropriate timing and sequence in terms of restoring efficacy of immunotherapy in resistance events (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%